Investigating training impact on farmers' perception and performance - Mohd Noor, Khairul Baharein; Dola, Kamariah (Center for Promoting Ideas, 2011)
This research paper investigates the impact of training on Malaysian livestock farmers’ capabilities and performance level in their farm practice. A total of 323 farmers and training personnel participated in this study as respondents. A multi-stage approach was used where data were primarily collected using mail survey followed by telephone survey and personal face-to-face feedback. This was then supported by semi-structured interviews with identified individuals on the basis of purposive sampling. Analysis of findings suggested that on a general account a positive trend has emerged from this study indicating the effectiveness of the training programs although with range of variations of benefits gained by the farmers. A majority of the respondents agreed that the program have been useful and had made them become better farmers. The impact of training on farmers can be summarized into six major benefits according to priority: (i) increased in work quality (ii) increased in farm products (iii) cost savings (iv) time savings (v) increased in income and finally (vi) increased in networking. Training provided to the farmers has not only helped them improved their individual capabilities (SKAs), but more important, boost their morale and motivation that clearly contributed to their positive performance level.